2009
DOI: 10.1007/s11146-009-9221-z
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency in Welfare Inferences from Distance Variables in Hedonic Regressions

Abstract: Hedonic, Distance, Sensitivity analysis, R0, Q5, C8,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(114 citation statements)
references
References 12 publications
3
105
6
Order By: Relevance
“…It is consistent with Ross et al (2009) who showed through a simulation experiment that welfare inferences should not be estimated using distance variables because of serious identification problems. While multiple distance variables or a trend surface can identify an observation's relative location, it is not possible to robustly isolate the MWTP associated with particular landmarks from those that are correlated in space but not included in the model.…”
Section: The Robustness Of Mwtp Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is consistent with Ross et al (2009) who showed through a simulation experiment that welfare inferences should not be estimated using distance variables because of serious identification problems. While multiple distance variables or a trend surface can identify an observation's relative location, it is not possible to robustly isolate the MWTP associated with particular landmarks from those that are correlated in space but not included in the model.…”
Section: The Robustness Of Mwtp Resultssupporting
confidence: 89%
“…A more comprehensive simulation-based comparison of OLS with spatial fixed effects and recent explicitly spatial methods is needed. Further, the challenge of obtaining reliable welfare estimates for distance-based amenities highlighted by Ross et al (2009) remains: Even when multiple distance points or trend surfaces are included in the model, as in this study, the welfare estimates across non-spatial and spatial methods remained particularly unstable compared to other locational attributes. The need to build on existing research to further incorporate flexible functional forms in hedonic models and measure locational attributes in more sophisticated ways (e.g., at different scales and taking interactions between locational attributes into account) was already mentioned above.…”
Section: Resultsmentioning
confidence: 88%
“…The table reports regression results for the three models mentioned earlier, that is the OLS 14 More suitable variables than distance may be devised. In a recent study, Ross et al (2009) show that the effects of distances to amenities on housing prices are generally not consistent indicators of the true price impact of that amenity. Due to space limitations and as our focus is on the acreage of open space, we do run any further tests about any alternative of the distance variable.…”
Section: Resultsmentioning
confidence: 97%
“… More suitable variables than distance may be devised. In a recent study, Ross et al. (2009) show that the effects of distances to amenities on housing prices are generally not consistent indicators of the true price impact of that amenity.…”
mentioning
confidence: 99%
“…Measuring park density combines the commonly used distance and size measures in other studies rather than examining those relationships separately. That construct of proximity alleviates potential identity problems associated with distance to amenity measures (see Ross, Farmer, & Lipscomb, 2011).…”
Section: Analytical Frameworkmentioning
confidence: 99%